Community structure of echinoderms in selected reef areas in Taklong Island, Guimaras. - Salva, Julie Clarice
Despite the great diversity of marine invertebrates within Taklong Island, only a few existing ecological studies have been directed to reef-associated echinoderms. The objective of this study was to provide baseline information regarding the community structure of echinoderms in Talisay, Kalirohan, Banago, and Piagau reef areas. Data was collected in three 2x50-meter belt transect per site. The total area surveyed was 1200m2 where 91 individuals belonging to 16 species were encountered. Of these, there were 4 Asteroide, 4 Echinoids, 3 Crinoids, 3 Holothuroids, and 2 Ophiuroids. Diadema setosum was the most abundant with a total of 35 individuals and densest with the mean density of 12 ind. 100m-2. Out of the five classes, echinoids were the most abundant with a total of 43 individuals. Piagau and Banagao reef sites which are classified as ?good? healthy reef based on live coral cover (>50% bu <75%), have high echinoderm diversity. Due to the varying spawning season and activity time of reef-associated echinoderms, it is recommended that temporal distribution be studied. Furthermore, sampling should also be made during nighttime to compare the abundance of echinoderm species from the diurnal ones.